LARVA CACING BERKEPALA DURI Monoliformis dubius (ACANTHOCEPHALA: MONOLIFORMODAE) PADA KECOA, Periplaneta ameticana DI PERMUKIMAN KODYA BOGOR - Endang Purwaningsih (Research Center for Biology-Indonesian Institute of Sciences, 1998)
-